The IMIA Strategic Plan - Towards IMIA 2015 - Murray, P.J.; (Interim Vice President Strategic Planning Implementation, International Medical Informatics Association) (Yearbook of Medical Informatics, 2008)
Objective To present the IMIA Strategic Plan, ‘Towards IMIA2015’, to a wide audience within and outside the ‘IMIA family’, so as to aid in turning the vision of the plan into reality.Methods IMIA, the International Medical Informatics Association, unanimously adopted the IMIA Strategic Plan, ‘Towards IMIA2015’, at its 2007 General Assembly meeting in Brisbane, Australia. The wide dissemination of this plan is one of the first stages in the developing IMIA Transition Plan, which will develop a roadmap and specific projects for implementing the strategy. The IMIA Strategic Plan is presented here, and we welcome dialogue with all who wish to work with IMIA to achieve the vision and the strategic goals, of providing leadership and expertise to the multidisciplinary health focused community and policy makers to enable the transformation of healthcare to improve the health of the world population.Results and conclusions IMIA and its members are now engaged in work to support implementation of the IMIA Strategic Plan. IMIA invites all with an interest in our activities to work with us towards achieving the strategic goals and making the vision a reality by 2015.
Keywords: International Medical Informatics Association; IMIA; health informatics; medical informatics; strategy